Decentralization, democracy, and development : recent experience from Sierra Leone - Zhou, Yongmei; World Bank. (Washington, D.C. : World Bank, 2009)
This publication addresses the question of whether political, fiscal , and administrative decentralization improves government effectiveness and the debate on whether it is a viable and desirable state-building strategy for post-conflict countries. The publication is a collection o f eight papers written by authors who were closely involved in the dece ntralization reform process in Sierra Leone from 2003-07. During this p eriod, Sierra Leone's government established elected district and urban councils across the country, transferred certain responsibilities for primary services and local investment and some financial resources to t he new councils, and invested heavily in building the administrative in frastructure and capacity of the local councils. Compared to most other Sub-Saharan African countries that have embarked upon decentralization , Sierra Leone's progress in building local government capacity and res tructuring the fiscal system is enviable. The authors conclude that imp roved security and public services are possible in a decentralizing cou ntry and Sierra Leone's progress would not have been possible without s ignificant effort at fiscal decentralization and intensive investment i n local government capacity building. The most critical ingredient for this reform process is the leadership team in charge of promoting the n ew institutional framework and their persistent effort to achieve quick improvement in the local government system and public services.--Publi sher's description.
Introduction / Yongmei Zhou -- Establishing the legislative, politic al and administrative framework for local government and decentralizati on in Sierra Leone / Emmanuel Gaima -- Fiscal decentralization : buildi ng the financial capacity of local governments / Adams Sanpha Kargbo -- Administrative decentralization : building the non-financial capacity of local governments / Alhassan Kanu -- Decentralization in practice / Katherine Whiteside Casey -- Impact of decentralization on public servi ces : evidence to date / Elizabeth Foster and Rachel Glennester -- Civi c engagement in local governance / Yongmei Zhou and Ye Zhang -- Landsca pe of local authority in Sierra Leone : how traditional and modern just ice and governance systems interact / Ryann Elizabeth Manning -- Reflec tions and conclusions on positives and problems resulting from devoluti on to date / Emmanuel Gaima.
Includes bibliographical references.
Keywords: Decentralization in government -- Sierra Leone; Local government -- Sierra Leone; Democracy -- Sierra Leone; Sierra Leone -- Politics and government -- 1961-